Trends as Future Prompts in the Anticipatory Design Practice. (August 2020) - Celi, Manuela; Colombi, Chiara
Highlights: Metadesign practice as an example of how future's knowledge got made in the design field. Analysis shows that trend are meta-narration of the design activity and a tool for communicating and sharing contents Trend research is incorporated into the innovation generation process, through the Metadesign approach. Trend research, differing from trend analysis, has a cognitive orientation. Results highlight that trends'use combine the different depths of futures' inquiry with the design practice's one.